La cavidad cerrada en las lesiones abiertas - Dasso, Héctor (1938)
The authors come to the following conclusions: 1st The closed cavity of Méndez is the ideal biological treatment of suppurating lesions. 2nd The mecanism of its cure rests in the contact of the specific haptinas (antibodies) with the antigen (germs or, toxins) in the locality of the lesion. 3rd The object of the «closed cavity» is to retain the humors (moisture) in order to facilitate the process of peptization. 4th It is necessary to differentiate the inflammatory exudates in to puri- form and purulent. 5th The substances employed in the advised method have no curative properties and only contribute to a better occlusion of the lesions.